(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluation of the effect of the traditional medicine remedy «Bo than sinh tinh thang» on the cavernosum pressure of male Wistar rats. Method: To study on 40 male Wistar rats 24-week-old oral «Bo than sinh tinh thang» remedy extract only once, after anesthesia and measured ICP (intracavernous pressure) before taking the drug. Measurement of ICP, arterial blood pressure by powerlab system before and after stimulating cavernous nerves at the time before and after taking drugs 15 minutes, 30 minutes, 45 minutes. Results: “Bo than sinh tinh thang” increased basal ICP at 30 minutes and 45 minutes after taking drugs (p <0.05); increases ICP max, response time and ICP max/MAP (p <0.01) after electrical stimulation on the cavernous nerve at 15 minutes, 30 minutes and 45 minutes after taking drugs compared with before taking drugs as well as the control, but did not affect mean arterial pressure in rats. The effects of this remedy were equivalent to a Sildenafil dose of 10 mg/kg. Conclusion: “Bo than sinh tinh thang” remedy increase intracavernous pressure on anesthetic Wistar rats and does not affect arterial blood pressure.